Spatial parameters for the development of floating wind farms in Greece - Dimitris Melissas; Evangelos Asprogerakas (European Journal of Geography)
The interest in offshore wind farm markets has recently turned to the use of the strong wind power that can be found in deep-sea marine areas with the use of innovative technology in floating wind farms. This activity attracts the interest of economic actors globally, with prevention still necessary to avoid potential conflicts with other maritime activities and protect sensitive local marine ecosystems. The main research interest of this study focuses on the role that the particular characteristics of the local legal framework can have on the spatial planning of activities. The steps taken in this gradual approach include current spatial planning practice, case law and the country’s experience in related projects. Concluding, an example of the possible spatial planning of FWFs, based on the current tools available in the country’s spatial planning system, is provided.